Security and management policy specification. - Sloman, M. (IEEE Network : the magazine of global information exchange)
Policies are rules governing the choices in behavior of a system. They are increasingly being used as a means of implementing flexible and adaptive systems for management of Internet services, networks, and security systems. There is also a need for a common specification of security policy for large-scale multi-organizational systems where access control is implemented in a variety of heterogeneous components. In this article we survey both security and management policy specification approaches, concentrating on practical systems in which the policy specification can be directly translated into an implementation